The fiction of postmodernity - Baker, Stephen, Ph. D. (Edinburgh University Press, 2000)
"The Fiction of Postmodernity is a significant and accessible new study of the relation of postmodern fiction to theories of the postmodern. Contemporary works of fiction by novelists such as Don DeLillo, Toni Morrison, Salman Rushdie, Thomas Pynchon and Martin Amis are viewed in relation to critiques of the 'culture industry', analyses of the 'postmodern condition' and theories of simulacra. The work of influential theorists of the postmodern - such as Theodor Adorno, Jean-Francois Lyotard, Fredric Jameson and Jean Baudrillard - is explained and compared."--Jacket